Price Effect and Physical Evidence on Purchase Decision at Rooftop Coffee Bandung - Alfiyatur Rahmah; Nuslih Jamiat (Budapest International Research and Critics University, 2022)
The rapid development of business in the culinary field which results in changes in consumer behavior, business people who are engaged in the same field must be able to implement strategies that can maintain and develop their business. One of the fast-growing culinary businesses today is a café. One of the cafes that can be considered quite famous in Bandung is Rooftop Coffee. In order for its business to remain competitive, Rooftop Coffee must develop a marketing strategy that can attract potential customers and retain old customers, but in the past year Rooftop Coffee is experiencing an increase and decrease in sales. significant. This shows that there is a decrease in consumer purchasing decisions on Rooftop Coffee. However, the service marketing strategy that has been carried out by Rooftop Coffee is considered to be less effective, this is shown by the presence of several negative reviews and complaints through the digital platform regarding Rooftop Coffee, especially on the dimensions of price and physical evidence. This research was conducted to determine the effect of Price and Physical Evidence on Purchase Decisions at Rooftop Coffee Bandung. This study uses quantitative methods of descriptive research with multiple linear regression analysis techniques. The sampling technique used was non-probability sampling, the type of accidental sampling with the number of samples used by as many as 100 respondents who were Rooftop Coffee consumers who had visited and purchased Rooftop Coffee products. This test was carried out using the help of SPSS 26. Based on the results of descriptive analysis in this study, the price variable was included in the good category with an average percentage of 75.68%, while the Physical Evidence as a whole had an average percentage of 77.63% and the overall Purchase Decision variable. overall has an average percentage of 52.28%. The results of this study are the influence of Price and Physical Evidence on Purchase Decisions on Rooftop Coffee with a t-test result of tcount Price (X1) 2.711 > table 1.987 and for Physical Evidence (X2) 6.732 > table 1.987 and by using the f test it can be seen that the price and physical evidence simultaneously affect the purchase decision. by 66% while 34% is influenced by other factors that can influence purchasing decisions, one of which is other factors that are not examined such as location, people, promotions, products and processes.